12ab+6ab-9bc=

Simple and best practice solution for 12ab+6ab-9bc= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12ab+6ab-9bc= equation:


Simplifying
12ab + 6ab + -9bc = 0

Combine like terms: 12ab + 6ab = 18ab
18ab + -9bc = 0

Solving
18ab + -9bc = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9bc' to each side of the equation.
18ab + -9bc + 9bc = 0 + 9bc

Combine like terms: -9bc + 9bc = 0
18ab + 0 = 0 + 9bc
18ab = 0 + 9bc
Remove the zero:
18ab = 9bc

Divide each side by '18b'.
a = 0.5c

Simplifying
a = 0.5c

See similar equations:

| 3x-16=4-2x | | 48s-34=48-28s | | 10-7=63 | | 51x-7=34x+163 | | .06x+x=5000 | | 3(4x)=27 | | 35-10= | | (x+5)(x+7)=105 | | sin(2x)=cos(5x) | | b^2-3=6 | | Y=9x-4xy+2x-xy | | 5r^2=10 | | 4y+20=15y-24 | | 3*ln(x+2)=9 | | 112+13p=86 | | 5x-16=x | | 5y-7=y+3 | | 4x-18=17+5 | | 56-6x=-28+8x | | 2x^2+8x-26=0 | | 5q^3(q^4-6q)= | | 96x+51y=6 | | ((6n^3)/(7x^5*y^2))/((3mn^20/(21x^3*y)) | | n/3=2n/6 | | 2x^2+4y=6 | | -2a+5a-12a= | | 5g-9-g=3G+12 | | 3(2p-1)=4p-11 | | 5/12x-12=48 | | 6x^7+22x^6+20x^5=0 | | 6x-13+9+5x=2x+1 | | 16=2/3y |

Equations solver categories